The analysis of students' ability to solve HOTS problems on the topic of sequences and series according to the Krulik and Rudnick stages - Aidha Ristiana Amalia Gayo; Nurcholif Diah Sri Lestari; Ervin Oktavianingtyas; Dinawati Trapsilasiwi; Randi Pratama Murtikusuma (State Islamic University of North Sumatra, 2025)
This study aimed to analyze the problem-solving abilities of low-performing students in addressing Higher Order Thinking Skills (HOTS) questions on sequences and series based on the stages proposed by Krulik and Rudnick. A descriptive qualitative approach was employed in this research. Thirty senior high school students completed a problem-solving test, from which two students who obtained the lowest scores were purposively selected for in-depth analysis and semi-structured interviews. Data were collected through written tests and interviews and analyzed using Miles' stages of qualitative data analysis. The results indicated that at the read and think stage, students were able to identify relevant information but demonstrated a limited understanding of the relationships among the given data. At the explore and plan stage, students attempted to organize information but encountered difficulties, particularly when dealing with sequence-related problems. At the select a strategy stage, students identified the appropriate formula; however, they showed hesitation in applying it correctly. At the find an answer stage, students performed computational procedures but often produced inaccurate results. Finally, at the reflect and extend stage, students tended to draw conclusions without verifying the correctness of their solutions. Overall, the main difficulties were evident in conceptual understanding, consistency in strategy application, and reflective evaluation.